Lesotho Rapid eTrade Readiness Assessment - United Nations Conference on Trade; Development (United Nations, 2020)
The eTrade Readiness Assessment of Lesotho focuses on examining seven key policy areas that are most relevant for e-commerce. Within each area, critical readiness gaps are identified and relevant recommendations are proposed to overcome barriers and bottlenecks to the growth of digital trade. The Lesotho Rapid eTrade Readiness Assessment is the eighteenth such assessment conducted by UNCTAD since the launch of the Programme in 2017. Lesotho has experienced an impressive economic growth over the past decade, with the country experiencing a Compound Annual Growth Rate of 3.6 percent annually since 2007, with its real gross domestic product (GDP) per capita increasing by 25 percent in the last decade. This growth was largely supported by increased diamond exports and the country is looking at economic diversification in a handful of sectors, such as mining, quarrying, textiles, and apparel. In this context, e-commerce can have the potential to boost the country's economic performance, and diversify sources of incomes, improving accessibility to customers, markets and trade information, all of which play a key role for development and graduation from the LDC category. Nevertheless, the conditions for success require the adoption of a series of fundamental reforms, such as having reliable and affordable infrastructure, the necessary legal and regulatory framework in place for payments, the appropriate solutions with regard to access to finance, and building the capacity to respond the needs of the digital economy.